30-DAY ALL-CAUSE READMISSION IN OLDER HEART FAILURE PATIENTS RECEIVING HOME VERSUS INPATIENT HOSPICE - Sheriff, H. (Innov Aging, 2017)
Background: Under Affordable Care Act hospitals may lose Medicare reimbursement for higher 30-day all-cause readmission, for which heart failure (HF) is leading cause, with ~25% HF patients being readmitted within 30 days of discharge. Hospice care may lower this risk. However, whether there is a difference between home hospice versus inpatient hospice remains unknown. Methods: In Medicare-linked OPTIMIZE-HF, of 25345 hospitalized HF patients 479 (2%) received post-discharge hospice (201 inpatient and 278 home) care. Propensity scores for inpatient hospice care, estimated for each of 479 patients, were used to match 125 inpatient hospice with 125 home hospice patients who were balanced on 46 baseline characteristics. The 250 matched patients had a mean age of 83 years, a mean EF of 36%, 61% were women, and 4% African American. Results: 30-day all-cause readmission occurred in 7% and 4% of matched inpatient hospice versus home hospice patients, respectively (HR, 2.73; 95% CI, 0.91–8.21). There was no difference in 6-month all-cause readmission (11% each). The risk of 30-day mortality was higher in the inpatient group, both at 30 days (87% vs. 82%; HR, 1.93; 95% CI, 1.39–2.67) and 6 months (93% vs. 87%; HR, 1.46; 95% CI, 1.11–1.91). Conclusion: Among hospitalized older patients with HF, both inpatient hospice and home hospice care were associated with low rates of 30-day all-cause readmission, which was numerically lower in the home hospice group at 30 days, but not at 6 months. Home hospice patients had lower risk of all-cause mortality at both times.